2015
DOI: 10.1007/s13365-015-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Rabies virus phosphoprotein interacts with mitochondrial Complex I and induces mitochondrial dysfunction and oxidative stress

Abstract: Our previous studies in an experimental model of rabies showed neuronal process degeneration in association with severe clinical disease. Cultured adult rodent dorsal root ganglion neurons infected with challenge virus standard (CVS)-11 strain of rabies virus (RABV) showed axonal swellings and reduced axonal growth with evidence of oxidative stress. We have shown that CVS infection alters a variety of mitochondrial parameters and increases reactive oxygen species (ROS) production and mitochondrial Complex I ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…We transfected the human embryonic cell line HEK-293T (HEK) with plasmids expressing RABV proteins and only the plasmid expressing the RABV phosphoprotein (P) increased Complex I activity and ROS levels, whereas none of the other rabies virus proteins increased Complex I activity or ROS levels (Kammouni et al 2015). We found co-localization of immunofluorescent staining for the RABV P and the voltage-dependent anion channel (VDAC) as a mitochondrial marker (Fig.…”
Section: Bases For Neuronal Injury In Rabiesmentioning
confidence: 92%
See 1 more Smart Citation
“…We transfected the human embryonic cell line HEK-293T (HEK) with plasmids expressing RABV proteins and only the plasmid expressing the RABV phosphoprotein (P) increased Complex I activity and ROS levels, whereas none of the other rabies virus proteins increased Complex I activity or ROS levels (Kammouni et al 2015). We found co-localization of immunofluorescent staining for the RABV P and the voltage-dependent anion channel (VDAC) as a mitochondrial marker (Fig.…”
Section: Bases For Neuronal Injury In Rabiesmentioning
confidence: 92%
“…This work strongly suggests that increased Complex I activity explains ROS overproduction, which was supported by Amplex Red assays for hydrogen peroxide production. We now have strong evidence that the RABV P physically interacts with Complex I and increases its activity resulting in increased ROS levels (Kammouni et al 2015).…”
Section: Bases For Neuronal Injury In Rabiesmentioning
confidence: 94%
“…Kammouni et al [115], using a proteomics approach, demonstrated that the phosphoprotein of rabies virus in in vitro mouse neuroblastoma cell lines causes mitochondrial dysfunction by complexing with the complex I subunit of mitochondria, thereby inducing oxidative stress via induction of reactive oxygen species.…”
Section: Bat Rabiesmentioning
confidence: 99%
“…However, cells infected with pathogenic strains do not undergo neuronal apoptosis but are rather affected by neuronal dysfunction, in contrast to the attenuated strains [56,58]. Pathogenic strains of RABV induce neuronal dysfunction, resulting in axonal and dendritic swelling and beading [58,82,83,84,85]. These morphological changes are thought to be sufficient to explain the onset of clinical signs and symptoms [83].…”
Section: Apoptosis: Detrimental or Beneficial To The Host?mentioning
confidence: 99%